Bis(2-hydroxyethylammonium) oxalate - Jordanovska, Vera; Naumov, Pancě; Kim, Moon-Jib; Lee, Han-Jun; Ng, Seik Weng (International Union of Crystallography (IUCr), 2000)
In bis(2-hydroxyethylammonium) oxalate, 2C2H8NO+·C2O42−, hydrogen bonds involving the hydroxy and ammonium groups connect the carboxyl O atoms of the oxalate anion into a three-dimensional network structure.